2023
DOI: 10.1042/cs20220654
|View full text |Cite
|
Sign up to set email alerts
|

Increased β1-adrenergic receptor antibody confers a vulnerable substrate for atrial fibrillation via mediating Ca2+ mishandling and atrial fibrosis in active immunization rabbit models

Abstract: Background: Autoimmune disorder is the emerging mechanism of atrial fibrillation (AF).The β1-adrenergic receptor antibody (β1-AAb) is associated with AF progress. Our study aims to investigate whether β1-AAbs involves in atrial vulnerable substrate by mediating Ca2+ mishandling and atrial fibrosis in autoimmune associated AF. Methods: Active immunization models were established via subcutaneous injection of the second extracellular loop (ECL2) peptide for β1 adrenergic receptor (β1AR). Invasive electrophysiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Electrophysiological parameters were measured in our previous work 11 . Briefly, the AERP was measured as follows:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrophysiological parameters were measured in our previous work 11 . Briefly, the AERP was measured as follows:…”
Section: Methodsmentioning
confidence: 99%
“…Electrophysiological parameters were measured in our previous work. 11 Briefly, the AERP was measured as follows: An output voltage, set at four times the pacing threshold and a pulse width of 0.5 ms, was administered. Stimulation was induced at a rate of 120 beats per minute using the S1S1 method (S1S1 interval = 200 ms) and maintained at an S1:S2 ratio of 8:1.…”
Section: Electrophysiologic Measurement In Vivomentioning
confidence: 99%
“…It has been shown that the β 1 -adrenergic receptor autoantibodies (β 1 -AAb) contribute to the development of autoimmunity-associated AF by targeting the functional domain on the second extracellular loop of the receptor itself. In vivo models revealed that β 1 -AAb contribute to atrial electrical instability through the activation of Ca 2+ /calmodulin-dependent protein kinase II (CaMKII) and phosphorylation of the ryanodine receptor (RyR2) [5]. These mechanisms prolong transient calcium refractoriness and promote arrhythmogenic and spatially discordant atrial alternans.…”
Section: Autoimmune Mechanisms Of Afmentioning
confidence: 99%
“…Induction of β1AR-AAbs aggravated atrial electrical instability and atrial fibrosis in rabbits. Further, in vitro experiments revealed that β 1 AR-AAb induced calmodulin kinase and ryanodine receptor 2 activation in atrial cardiomyocytes and the myofibroblasts phenotype formation [ 97 ]. β 1 AR-AAbs with thyroid hormone supplementation induced sustained AF in rabbits.…”
Section: β 1 Ar-aabs In the Other Cardiac Diseasesmentioning
confidence: 99%